Effect of ‘SMART health education model’ on knowledge and attitudes of school students in rural area about ‘Swachh Bharat Abhiyan of India’ and sanitation practices - Utpat, Nikita J.; Bogam, Rahul R. (International Journal Of Community Medicine And Public Health, 2017)
Background: India has been facing various sanitation problems like open defecation, insanitary toilets, improper waste disposal, manual scavenging etc. Poor sanitation in schools, particularly rural schools are health hazards and affects school attendance, retention and educational performance. Several studies reported poor knowledge about sanitation practices among school students in India, so there is need to inculcate good sanitation practices among them. ‘Swachh Bharat Abhiyan’ is national level health campaign of India which was launched on 2nd October 2014. The present study was first study to create awareness among school students about ‘Swachh Bharat Abhiyan’ as well as sanitation practices through ‘SMART Health Education Model’. Methods: An interventional study was conducted in one of the randomly selected public schools in rural field practice area of Bharati Vidyapeeth University Medical College, Pune. The study participants were 100 students belonging to 5th and 6th class and they were exposed to structured ‘SMART Health Education Model’. Entire data from pre and post intervention questionnaire was entered into ‘Microsoft Office Excel Sheet’ and analysed by using ‘Paired t test’. Results: Significant improvement in knowledge about sanitation practices was found after applying ‘SMART Model’ (Pre-test mean marks: 4.17, post-test mean marks: 9.52, t = 24.31, p<0.001). The study reported favourable attitudes of participants towards ‘Swachh Bharat Abhiyan’. Conclusions: It indicates that even a simple intervention like ‘SMART Model’ can make significant change in knowledge of school students about personal and environmental hygiene.